Influence of Clay on Time Domain Induced Polarization - Yatini Yatini (Indonesian Journal of Science and Technology, 2018)
The main problem in mineral exploration is how to determine the existence of deposits at subsurface based on resistivity and chargeability parameters. Clay almost exists in rocks. Here, this study was to understand the influence of clay on time domain induced polarization. To clarify the clay parameters, field physical modeling was conducted. The results showed physical modeling data of 20-cm diameter spherical target with a total content of 28.3% of iron did not show any significant response. The high content of clays on the medium used in field physical modeling seems to be the main reason for the change in sample. In the case of the subsurface spherical model that is near to the soil medium, the presence of clay leads to the medium resistivity value to be identical to the target value. As a consequence, the resistivity response can not be identified clearly. The chargeability between the medium and the target remains small but the chargeability response remains constant.